2010
DOI: 10.1089/end.2010.0068
|View full text |Cite
|
Sign up to set email alerts
|

Resorbable Clip Migration Resulting in Ureteral Obstruction and Sepsis After Laparoscopic Pyeloplasty

Abstract: We report a rare complication of Lapra-Ty clip migration into the ureter with resultant obstruction and sepsis after dismembered laparoscopic pyeloplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Brusky and Tran5 reported a case of clip migration to the ureter following pyeloplasty. Shin et al , Yi et al , Mora et al , Tugcu et al , and Tunnard and Biyani reported clips that migrated to the urine bladder following radical prostatectomy 6–10.…”
Section: Discussionmentioning
confidence: 99%
“…Brusky and Tran5 reported a case of clip migration to the ureter following pyeloplasty. Shin et al , Yi et al , Mora et al , Tugcu et al , and Tunnard and Biyani reported clips that migrated to the urine bladder following radical prostatectomy 6–10.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 As a result, the diagnosis is difficult to ascertain on the basis of imaging alone. Most often, they can be diagnosed and treated endoscopically with either ureteroscopy or percutaneous nephroscopy.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…This device was first used in plastic surgery, but it has spread widely among other surgical fields . Its application in veterinary medicine has resulted in only a few reports, but its use has already been associated with reduced operative times . Several strategies have been described to avoid the reduction of tension during continuous anastomoses and decrease the number of intracorporeal knots, including the use of specific clips, such as LapraTy ® (Ethicon, Somerville, NJ) or Hem‐O‐Lok ® (Weck Closure Systems, Research Triangle Park, NC).…”
Section: Discussionmentioning
confidence: 99%